Análise do impacto do raciocínio clínico reflexivo estruturado, adicionado ou não de diretrizes complementares, na acurácia diagnóstica de estudantes de medicina e de médicos residentes em pediatria - Rachel Aparecida Ferreira Fernandes (2019)
BACKGROUND: Adding guidance by cueing reflection or providing modelling of reflection increased the beneficits of structured reflection for medical diagnostic competence, while practising the diagnosing of cases. The present study investigated if additional instructional guidance provide different effects according to the students' formation stage and Pediatric residents in solving cases with different complexities. METHODS Eighty Year 3 and 62 Year 6 medical students in addition to 64 first-year pediatric residents and 63 second-year residentes participated in a three-phase randomized experiment. During the training phase, participants diagnosed twelve clinical cases under different experimental conditions: free structured reflection; cued reflection and modelled reflection. In an immediate test, immediately after the training fhase, and a delayed test, after one week later, participants diagnosed new sets of twelve diferente cases, six of which presented diseases they had studied during the training phase (four routine diseases in the clinical practice and two rare diseases). The impact of the evaluated teaching strategies on diagnostic accuracy was measured by the degree of precision achieved by the study groups in solving recurrent disease cases at all stages of the study. RESULTS: Repeated-measures of variance (ANOVA) of mean scores for diagnostic accuracy (range 0-1) showed a significant main effect of experimental condition (p <0.001), year of training (p <0.001), performance moment phase (p <0.001), and the complexity of the cases (p <0.001). The use of structured reflection plus instructional guidelines resulted in a significant improvement in the immediate test for all cases (p <0.001), regardless of the participants' training phase, thus proving to be effective at this time of evaluation. In the delayed test, this benefit was maintained in the solution of routine cases (p <0.001). In solving rare cases, the benefit was maintained only for more experienced learners (p <0.001). The modelled reflection group and cued reflection group did not differ in performance (p> 0.05), but both outperformed the free reflection group (p <0.001), regardless of the training phase and complexity of cases. CONCLUSIONS: The use of additional guidelines for structured reflection has a better impact on learning than their use in their original form and can represent a useful strategy for clinical teaching, regardless of the student's training stage and pediatric training. Teaching with full or partial worked examples appears to be equally effective approaches.